MuSyC dosing of adjuvanted cancer vaccines optimizes antitumor responses - Taylor, David; Meyer, Christian T.; Graves, Diana; Sen, Rupashree; Fu, Juan; Tran, Emily; Mirza, Bilal; Rodriguez, Gabriel; Lang, Cara; Feng, Hanwen; Quaranta, Vito; Wilson, John T.; et al. (Frontiers in Immunology, 2022)
With the clinical approval of T cell-dependent immune checkpoint inhibitors for many cancers, therapeutic cancer vaccines have re-emerged as a promising immunotherapy. Cancer vaccines require the addition of immunostimulatory adjuvants to increase vaccine immunogenicity, and increasingly multiple adjuvants are used in combination to bolster further and shape cellular immunity to tumor antigens. However, rigorous quantification of adjuvants’ synergistic interactions is challenging due to partial redundancy in costimulatory molecules and cytokine production, leading to the common assumption that combining both adjuvants at the maximum tolerated dose results in optimal efficacy. Herein we examine this maximum dose assumption and find combinations of these doses are suboptimal. Instead, we optimized dendritic cell activation by extending the Multidimensional Synergy of Combinations (MuSyC) framework that measures the synergy of efficacy and potency between two vaccine adjuvants. Initially, we performed a preliminary in vitro screening of clinically translatable adjuvant receptor targets (TLR, STING, NLL, and RIG-I). We determined that STING agonist (CDN) plus TLR4 agonist (MPL-A) or TLR7/8 agonist (R848) as the best pairwise combinations for dendritic cell activation. In addition, we found the combination of R848 and CDN is synergistically efficacious and potent in activating both murine and human antigen-presenting cells (APC) in vitro. These two selected adjuvants were then used to estimate a MuSyC-dose optimized for in vivo T cell priming using ovalbumin-base peptide vaccines. Finally, using B16 melanoma and MOC1 head and neck cancer models, MuSyC-dose based adjuvating of cancer vaccines improved the antitumor response, increased tumor-infiltrating lymphocytes, and induced novel myeloid tumor infiltration changes. Further, the MuSyC-dose based adjuvants approach did not cause additional weight changes or increased plasma cytokine levels compared to CDN alone. Collectively, our findings offer proof-of-principle that our MuSyC-extended approach can be used to optimize cancer vaccine formulations for immunotherapy.